Preoxidation and Activation of the Lignin Char: Carbonization and Oxidation Procedures - Saloua Sebbahi; Adnane Ahmido; Fatima Kifani-Sahban; Souad El Hajjaji; André Zoulalian (Journal of Engineering)
A comprehensive process of pretreatment and oxidation of lignin char was developed to optimize the production of activated carbon. The lignin char was obtained by carbonization of lignin under nitrogen at 600°C for 2 hours. The optimum time and temperature used to oxidize the char without destruction were, respectively, 6 hours and 245°C. The oxygen improves the reactivity of the sample in CO2 and evolved the sample of a thermoplastic behaviour to a thermosetting behaviour. The oxygenation in air of the lignin char does not change the mode of deformation acquired by the material during the carbonization. The preoxidized coal reacts more than the nonoxidized coal during the CO2 activation, whereas the reduction in volume in the first case is smaller than in the second. The preoxidized and then activated carbon shows the formation and the development of microporosity at the expense of macroporosity. This microstructure is one of the main characteristics of activated carbon, which can be used as adsorbent for different pollutants.